"Análisis del Proceso Administrativo de los servicios que brinda EWL departamento médico de la Escuela Superior Politécnica Agropecuaria de Manabí Mauel Félix López" - Guzmán Alónzo, Patricia Marcela (2010)
This is a graduation thesis that has been elaborated by Guzman Alonzo Patricia Marcela, and Ouiroz intriago Maria Monserrate who will obtain the Title of Ingeniera in Administration of agreement Companies AL REGLAMENTO FOR THE ELABORATION OF THESIS OF DEGREE OF THIRD LEVEL of the Agricultural Polytechnic Superior School of Manabi Manuel Felix LOpez ESPAM MEL. The document has been carried out under the tutorship of the Engineer Angel Alberto Velez Mero. The topic of the thesis is "ANALYSIS OF THE ADMINISTRATIVE PROCESS OF THE SERVICES THAT OFFERS THE MEDICAL DEPARTMENT OF THE AGRICULTURAL POLYTECHNIC SUPERIOR SCHOOL DE MANABI MANUEL FELIX LOPEZ" it has been product of a diagnosis with which you could determine that the processes carried out in the department required a bigger control and efficiency, for the effect the authors considered pertinent to establish five chapters. . in the first chapter it is presented to the Medical Department of the Agricultural Polytechnic Superior School of Manabi Manuel Felix Lopez indicating their location and antecedents. The second chapter wide information has more than enough generalities of the administrative process. The methodological design is sketched in the third chapter. The results are shown by means of the surveys applied the students, community, employees and educational of the Agricultural Polytechnic Superior School of Manabi Manuel Felix LOpez in relation to the services that it offers the Medical Department in the fourth chapter. Finally there are the conclusions, recommendations, bibliography and annexes as fundamental part of all work of investigation.